Human Platelet Lysate Maintains Stemness of Umbilical Cord-Derived Mesenchymal Stromal Cells and Promote Lung Repair in Rat Bronchopulmonary Dysplasia - Liao, Guilian; Liao, Yan; Li, Duanduan; Fu, Zeqin; Wu, Shiduo; Cheng, Danling; Ouyang, Qiuxing; Tang, Zan; Zeng, Guifang; Liang, Xiao; Xu, Shaokun; Hu, Junyuan; et al. (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal cells (MSCs) show potential for treating preclinical models of newborn bronchopulmonary dysplasia (BPD), but studies of their therapeutic effectiveness have had mixed results, in part due to the use of different media supplements for MSCs expansion in vitro. The current study sought to identify an optimal culture supplement of umbilical cord-derived MSCs (UC-MSCs) for BPD therapy. In this study, we found that UC-MSCs cultured with human platelet lysate (hPL-UCMSCs) were maintained a small size from Passage 1 (P1) to P10, while UC-MSCs cultured with fetal bovine serum (FBS-UCMSCs) became wide and flat. Furthermore, hPL was associated with lower levels of senescence in UC-MSCs during in vitro expansion compared with FBS, as indicated by the results of β-galactosidase staining and measures of senescence-related genes (CDKN2A, CDKN1A, and mTOR). In addition, hPL enhanced the proliferation and cell viability of the UC-MSCs and reduced their doubling time in vitro. Compared with FBS-UCMSCs, hPL-UCMSCs have a greater potential to differentiate into osteocytes and chondrocytes. Moreover, using hPL resulted in greater expression of Nestin and specific paracrine factors (VEGF, TGFβ1, FGF2, IL-8 and IL-6) in UC-MSCs compared to using FBS. Critically, we also found that hPL-UCMSCs are more effective than FBS-UCMSCs for the treatment of BPD in a rat model, with hPL leading to improvements in survival rate, lung architecture and fibrosis, and lung capillary density. Finally, qPCR of rat lung mRNA demonstrated that hPL-UCMSCs had lower expression levels of inflammatory factors (TNF-ɑ and IL-1β) and a key chemokine (MCP-1) at postnatal day 10, and there was significant reduction of CD68+ macrophages in lung tissue after hPL-UCMSCs transplantation. Altogether, our findings suggest that hPL is an optimal culture supplement for UC-MSCs expansion in vitro, and that hPL-UCMSCs promote lung repair in rat BPD disease.